Benign retroperitoneal schwannoma : a rare cause of flank pain - Sariyuce, Oguzhan; Ozsan, Ozcan; Muezzinoglu, Bahar; Ozkan, Semih; Gurpinar, Tayfun; Aydin, Engin (Annals of Medical Research, 2021)
None